Innovations in cardiac conduction system research: Female frontiers and global disparities - Abimbola J. Aminu; Kenisuomo C. Luwei; Halina Dobrzynski (Elsevier, 2024)
Background: The cardiac conduction system (CCS) initiates and propagates electrical impulses across the heart. Scientists of both sexes have played unprecedented roles in discovering the CCS and advancing our anatomical, electrophysiological, and molecular understanding of the CCS in health and disease. Here, we review the underrepresentation of women in cardiac research and global disparities in cardiacresearch, specifically CCS research.Despite the invaluable contributions of women in advancing our cardiac understanding, sex disparities exist. There is a stark underrepresentation of women in cardiac academia, the cardiac industry, and cardiac-related associations globally. However, female researchers have played pivotal roles in expanding our anatomical and molecular understanding of the CCS. In addition to this sex disparity, there is a global disparity in the output and funding of cardiac research. Even though low- and lower-middle-income countries account for over half of cardiovascular deaths worldwide, they contribute to less than 3% of the global cardiovascular research output. Aims: This review aims to provide insights into the roles women researchers have played in transforming the landscape of CCS research. It also aims to shed light on the global disparities in cardiac research. The main goals are to draw attention to women's innovative contribution to cardiac research, to provide initiatives to create equal opportunities for women in cardiac academia and industry, and to enhance global cardiac research. Conclusions: This review shows that there are innovative contributions by women researchers in advancing our understanding of the anatomy, function, and physiology of the CCS. It also shows that there is an underrepresentation of women at various levels: in academia and industry. Furthermore, we describe the global disparities in cardiac research owing to various contributing factors, such as underfunding. This review provides valuable initiatives (such as conference invitations and research funding assessments) that could be implemented in order to create a more inclusive future in global cardiac research.